2018
DOI: 10.1136/heartasia-2018-011068
|View full text |Cite
|
Sign up to set email alerts
|

Association between apparent temperature and acute coronary syndrome admission in Rasht, Iran

Abstract: ObjectiveOur objective was to assess the relations between apparent temperature and incidence of acute coronary syndrome (ACS) in Rasht, Iran.MethodsWe used a time-series analysis to investigate the relationship between apparent temperature and hospital admission from 2005 to 2014. Distributed lag non-linear models were used to estimate the association between ACS hospitalisation and apparent temperature. To examine the high-temperature effect on ACS hospital admission, the relative risk of ACS hospital admiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The incidence of CAD has increased significantly in recent years in Iran. The prevalence of cardiovascular diseases (CVDs) is about 45% in Iran so that it is significantly higher than in Western countries [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of CAD has increased significantly in recent years in Iran. The prevalence of cardiovascular diseases (CVDs) is about 45% in Iran so that it is significantly higher than in Western countries [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The result was consistent with Michelozzi et al on temperature and CVD related admission in 12 European cities [ 50 ]. The decrease in risk with temperature was also demonstrated in Rasht for the association between apparent temperature and acute coronary syndrome [ 18 ]. However, numerous studies have found that extremely low temperatures can significantly increase hospital admissions and mortality [ 20 , 21 , 39 , 45 , 51 ], and most current study on low temperature and CVD related admissions are centered around extreme cold.…”
Section: Discussionmentioning
confidence: 82%
“…Currently, most studies focused on the temperature-mortality link [ [5] , [6] , [7] , [8] , [9] ], and some have identified the harvesting effect [ 10 – 13 ]. Studies on temperature and CVD related admissions, however, are limited and inconsistent in developing countries [ [14] , [15] , [16] ], and positive, negative, or no relationships were reported between temperature and CVD related admissions [ [16] , [17] , [18] , [19] ]. A J-shaped relationship was found in the study of temperatures on hospital admissions related to cardiovascular and cerebrovascular diseases in Shanghai [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have analyzed the association between apparent temperature and the incidence of ACS, and the results have varied. In Iran, Moghadamnia et al showed an increase in the number of ACS on days with a high apparent temperature, while Wichmann et al identified that an increase in Tapp max (the daily 3-h maximum apparent temperature) was associated with a decrease in the incidence of AMI in the cold months [ 48 , 49 ]. In Beijing, China, the number of STEMI cases increased on days with a high apparent temperature, while the incidence of NSTEMI was higher on days with a low apparent temperature [ 50 ••].…”
Section: The Impact Of Meteorological Factors On Acute Coronary Syndromementioning
confidence: 99%